2018
DOI: 10.3390/molecules23051163
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in Silico Analysis of Ferric Reduction Oxidase (FRO) Genes Expression Patterns in Response to Abiotic Stresses, Metal and Hormone Applications

Abstract: The ferric reduction oxidase (FRO) gene family is involved in various biological processes widely found in plants and may play an essential role in metal homeostasis, tolerance and intricate signaling networks in response to a number of abiotic stresses. Our study describes the identification, characterization and evolutionary relationships of FRO genes families. Here, total 50 FRO genes in Plantae and 15 ‘FRO like’ genes in non-Plantae were retrieved from 16 different species. The entire FRO genes have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 103 publications
2
15
0
Order By: Relevance
“…Also, it could be worth studying the expression of these genes in different phytohormones and metals such as melatonin, 38 brassinosteroids, 39,40 strigolactones, 41 and iron stress. 42 These results may be valuable for the betterment of flower induction in plants.…”
Section: Resultsmentioning
confidence: 95%
“…Also, it could be worth studying the expression of these genes in different phytohormones and metals such as melatonin, 38 brassinosteroids, 39,40 strigolactones, 41 and iron stress. 42 These results may be valuable for the betterment of flower induction in plants.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, it is assumed that BBX members share a similar gene structure and functional characteristic within the same subfamily during the evolutionary relationship. Previously, it also has been reported that FRO gene family members in rice shared similar gene structure and functional characteristic during evolution in rice [37].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue specific expression is a common characteristic of the genes of a certain protein family in plants, which often reflects the functional collaborative and/or differences of the family members [ 51 ]. The preceding studies also shed light on developmentally regulated plant chitinases, clarifying their role in the specific physiological processes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%